2006
DOI: 10.1111/j.1365-2672.2006.02919.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of environmental Aeromonas in South East Queensland, Australia: a study of their interactions with human monolayer Caco-2 cells

Abstract: Aims: To investigate the prevalence of Aeromonas in a major waterway in South East Queensland, Australia, and their interactions with a gut epithelial model using Caco-2 cells. Methods and Results: A total of 81 Aeromonas isolates, collected from a major waterway in South East Queensland, Australia, were typed using a metabolic fingerprinting method, and tested for their adhesion to HEp-2 and Caco-2 cells and for cytotoxin production on Vero cells and Caco-2 cells. Aeromonas hydrophila had the highest (43%) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
2
24
2
1
Order By: Relevance
“…A number of toxin genes have been found in Aeromonas strains (10). Using a multiplex PCR to detect three enterotoxin genes (act, alt, and ast) of Aeromonas, Bin Kingombe and colleagues (12) showed that the act and alt genes were the most prevalent genes in different species of Aeromonas isolated from foods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of toxin genes have been found in Aeromonas strains (10). Using a multiplex PCR to detect three enterotoxin genes (act, alt, and ast) of Aeromonas, Bin Kingombe and colleagues (12) showed that the act and alt genes were the most prevalent genes in different species of Aeromonas isolated from foods.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical isolates of Aeromonas included three type culture strains (A. schubertii ATCC 43700, A. jandaei ATCC 49568, and A. veronii biovar veronii ATCC 35624) and two isolates obtained from a local metropolitan hospital (A. hydrophila RBH1 and A. hydrophila RBH2). The environmental strains were part of a bigger collection of Aeromonas strains isolated from a local river system, of which we included four strains previously shown to belong to different common groups and that were adherent to Caco-2 cells (10 Hemolysin production. Hemolysin production was determined visually after streaking Aeromonas strains on 5% horse blood agar plates (17), with Columbia agar base (Oxoid, Australia), following overnight incubation at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of virulence factors such as extracellular enzymes, siderophores, cytotoxic and cytotonic enterotoxins, haemolysins, endotoxins and cell associated factors such as S-layers, pili, polar and lateral flagella, outer membrane proteins and plasmids were associated with pathogenicity of Aeromonas spp. (Snowden et al, 2006;Pablos et al, 2009). Exotoxins are major virulence factors of Aeromonas spp.…”
Section: Introductionmentioning
confidence: 99%